Engineered ZnO and CuO Nanoparticles Ameliorate Morphological and Biochemical Response in Tissue Culture Regenerants of Candyleaf (Stevia rebaudiana) - Ahmad, Muhammad Arslan (Molecules, 2020)
Sustainable production of secondary metabolites in medicinal plants by artificial culturing on the industrial scale has gained worldwide importance. Engineered nanoparticles (ENPs) play a pivotal role in the elicitation of compounds of medicinal value. This investigation explores the influence of ZnO and CuO ENPs on in vitro roots formation, non-enzymatic antioxidant activities, and production of steviol glycosides (SGs) in regenerants of Candyleaf, Stevia rebaudiana. ENPs were applied in 0, 2, 20, 200, and 2000 mg/L of concentration in the MS medium containing plant shoots. The percentage of rooting induced was 91% and 94% by applying ZnO ENPs (2 mg/L) and CuO ENPs (20 mg/L), respectively. Moreover, at 2 mg/L of ZnO and 20 mg/L of CuO ENPs, the high performance liquid chromatography studies determined the significantly greatest content of SGs; rebaudioside A (4.42 and 4.44) and stevioside (1.28 and 1.96). Phytochemical studies including total flavonoid content, total phenolic content, and 2,2-diphenyl-1-picryl hydrazyl-free radical scavenging activity were calculated highest by the regenerants grown in 2 mg/L of ZnO and 20 mg/L of CuO ENPs dosage. Both ZnO and CuO ENPs at 200 mg/L and 2000 mg/L of concentration induced adverse effects on plant biomass, antioxidant activities, and SGs content up to 1.22 and 1.77 for rebaudioside A and 0.21 and 0.25 for stevioside. Hence, the biochemical and morphophysiological responses of Candyleaf were elicited as a defense against ZnO and CuO ENPs applied under threshold limit. This artificial biotechnological technique holds great promise for continued production of natural antioxidants on commercial scale and our study has further strengthened this impact.